NEO-SPEAK: A conceptual framework that underpins breaking bad news in neonatology - Seifart, Carola; Falch, Mirjam; Wege, Mirjam; Maier, Rolf F.; Pedrosa Carrasco, Anna J. (Frontiers in Pediatrics, 2022)
Objective: Breaking bad news in neonatology is a frequent and difficult challenge. Although there are guidelines for communicating with parents in pediatrics and neonatology, the specific framework for breaking bad news in neonatology has not been studied in more detail. Therefore, we aimed to identify determinants that are important for successful managing breaking bad news in neonatology from professionals’ perspective and to develop a conceptual framework that underpins this challenging task. Methods: We conducted seventeen semi-structured interviews with senior neonatologists of six perinatal centers of the highest level of care in Germany. The transcripts were analyzed according to Mayring’s method of qualitative content analysis using inductive and deductive coding. Results: Eight determinants of breaking bad news in neonatology could be identified from the interviews. From these, we developed the conceptual framework NEO-SPEAK. The first three determinants, Neonatal prognostic uncertainty, Encounter in (triangular-)partnerships, Organization and teamwork (NEO) are directly related to the specific care situation in neonatology, whereas the others, Situational stress, Processuality, Emotional burden, Attention to individuality, Knowledge and experience, play a role for difficult conversations in general, but are subject to special modifications in neonatology (SPEAK). In addition to determinants that are necessary for news transfer, the results show that the context in neonatology as well as reciprocal effects on the team and the individual level of the physicians are important influencing factors in successful managing breaking bad news. Conclusion: On the one hand, the constitutional framework NEO-SPEAK shows which special aspects play a role in neonatology for the delivery of bad news, and on the other hand, it can help to identify and consider these aspects in clinical routine and training. Considering or reinforcing each NEO-SPEAK element when planning or delivering bad news can significantly improve communication with parents of critically ill or premature newborns and support the resilience of the caring team.